Pemanfaatan Tanaman Sagu (Metroxylon Sp.) oleh Kelompok Tani Hutan (KTH) Mandiri Sejati sebagai Sumber Ketahanan Pangan di Desa Loleo Kota Tidore Kepulauan - Hikmah, Nur; Ashari, Reyna; Irmayanti, Laswi; Wijayanti, Andi Ridha Yayank; Muhammad Rhafly Husen (Fakultas Kehutanan, Universitas Hasanuddin, 2022)
ABSTRACT: Non-timber forest products (NTFPs) are natural resources that are widely available in Indonesia and are used by the community as their livelihood. NTFPs that have a high social, economic, and cultural role in the community are sago palms (Metroxylon sp.). Sago is a carbohydrate-producing plant that has the potential to support the national food security improvement program. People in Tidore Islands, North Maluku generally consume sago as a daily food source. The development of sago in Tidore Islands is carried out by many parties, including the Tidore Islands Forest Management Unit (FMU), Forestry Depatment of North Maluku Province. Tidore Islands FMU assists and fosters three Forest Farmer Groups (FFG) that utilize NTFPs in the Forest Area, FFG Mandiri Sejati in Loleo Village is one of them and specifically utilizes sago. The purpose of this study was to determine the utilization and processing stages of sago in Loleo Village, Central Oba District. This research was conducted in Loleo Village from September to October 2021. Information related to the utilization and processing of sago was obtained through interviews with FFG members. The results showed that the main part of sago used was the stem which was processed traditionally and semi-mechanically to produce the final product of sago flour. The processing stages are sago cutting, grating the stem, filtering the sago grater, settling to obtain sago essence, and packaging the sago flor. Sago flour is still traditional and does not have a trademark as identity and differentiator from similar products on the market. Key words: NForest farmer group, Non timber forest product, Sago.